Evaluation Of Routing Protocols In Vanets - Chan, Wai Foo (2009)
The aim of this project is to study and evaluate vehicular ad-hoc network communication performance under realistic vehicular environments. To achieve this aim, we first study existing vehicular movement simulation tools and communication network simulation tools. We further develop a mobility pattern conversion tool, called SUMO2NS2. This tool translates vehicle movement traces (XML format) from SUMO ( a microscopic vehicular mobility simulation tool) to TCL format used in Network Simulator, Ns2.